An Analysis of Readiness of Teacher at MAN 2 Tapanuli Tengah In Facing Education Digital Transformation - Kurnia Arifah Pasaribu; Yunita Nadia (Indonesian Journal of Learning and Instructional Innovation, 2026)
The digital transformation in education requires teachers to be well-prepared in adopting technology as an effective teaching medium and method. The study aims to analyze the readiness of teachers at MAN 2 Tapanuli Tengah in facing the digital transformation of education, focusing on three key aspects: technological competence, attitudes and motivation, and supporting facilities and infrastructure. This research employs a quantitative approach with a descriptive method. Data were collected through questionnaires, interviews, and observations involving 35 teacher respondents. The results indicate that the overall readiness of teachers at MAN 2 Tapanuli Tengah is categorized as "Ready," with an average readiness in technological competence of 71.57%, attitudes and motivation at 79.43%, and facilities and infrastructure at 60.29%. These findings suggest that teachers possess adequate abilities and motivation to adapt to technological changes; however, the school needs to improve the availability of supporting facilities such as stable internet networks and digital devices. This study recommends continuous professional development for teachers and the enhancement of digital infrastructure to ensure the success of educational digital transformation in the madrasah environment.